Market Demand and Interest Profiling of Cebu Institute of Technology - University Students at The Onset of Online Learning - Polinar, Mark Anthony N.; Diano, Rafaeliza P.; Navares, Alein B.; Rago, Erlyn Ivy O. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This research was undertaken to understand the customer segments of the Cebu Institute of Technology- University using demographic, geographic, and socio-economic lenses. At the same time, this study also determined the students' technological capacity, technical capability, and willingness to enroll in the University's second summer term of 2020. The study used a descriptive research method to obtain data from 2,133 college students as the respondents using random sampling. Based on data gathered from the six colleges of the University, from first- to fifth-year levels, the closure of schools led them to go back to their provinces, resulting in the geographic distribution of respondents, with 48% situated outside of Cebu City. Moreover, one of the most significant impacts of the pandemic is the decline of combined household income from a mean of P34, 591.22 pre-pandemic to P23,923.85 during the pandemic when community quarantines were still enforced. Additionally, 72% of respondents have limited to moderate internet connectivity, sourced majorly from mobile data at 66% and personal or family-owned Wi-Fi at 50%. Widely used devices used at home were mobile phones at 97% and laptop computers at 56%. Recommendations included providing financial support through university-based and third-party programs and conducting marketing initiatives targeting the higher-income class to cushion the global economic crisis's negative financial impact.